PENGARUH PEMANFAATAN MEDIA MASSA DALAM PENERAPAN PENDIDIKAN KARAKTER SISWA - Fadhilah , Nurul (PT. Anagata Sembagi Education, 2024)
This research investigates the empowerment strategy of Al-Hikmah Orphanage in empowering foster children using a qualitative approach. The main purpose of this research is to analyze the efforts of Al-Hikmah Orphanage in empowering its foster children. Data collection was carried out by observation and probing interviews. The results showed that Al-Hikmah Orphanage runs several programs as an effort to empower foster children, including development in the fields of education, spirituality, physical and others.